Elucidation of structural abnormalities of the X chromosome using fluorescence in situ hybridisation with a Y chromosome painting probe. Issue 3 (March 1994) - Howell, R T; Millener, R; Thorne, S; O'Loughlin, J; Brassey, J; McDermott, A
Abstract : Particular regions of the X and Y chromosomes share DNA sequence homology to the extent that cross hybridisation occurs. Thus, chromosome painting with a whole Y chromosome probe consistently results in fluorescence on specific regions of the X chromosome as well as the complete Y chromosome. This phenomenon has been exploited to elucidate the structure of unusual X chromosome rearrangements, without Y involvement, in two females.